Food security stocks: Economic and operational issues - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2017)
The use of public food stocks for food security purposes is a hotly debated topic in international trade negotiations on agriculture within the World Trade Organization (WTO). Regardless of the legal standing of food stocks under the WTO legal framework, however, one must also consider the more substantive issue of whether public food stock programs make sense in terms of food security. This chapter discusses several economic and operational factors relevant to the design and use of public stocks for food security purposes in developing countries. Chapter 9 focuses on the legal issues related to the WTO agreements. Chapter 8 contains four sections. First is the consideration of several new circumstances in which these food security programs would operate, including changes in the world’s general economic and weather conditions, agricultural markets and policies, and food and nutrition security circumstances. The second section discusses general policy concepts related to food security and how food security stocks may fit into that policy framework. The third section covers different economic and operational issues specifically related to public food stocks and domestic food aid. A fourth and final section concludes the chapter.